PENGARUH PERCEIVED QUALITY DAN STORE ENVIRONMENT TERHADAP KEPUTUSAN PEMBELIAN ULANG MELALUI EXPERIENTIAL MARKETING SEBAGAI VARIABEL INTERVENING (Studi pada Pelanggan Pasaraya Sri Ratu Pemuda Kota Semarang) - Hafi, Ishmah Parameswari; Farida, Naili; Widiartanto, Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2015)
The research was distributed by the presence of Pasaraya Sri Ratu which rivaled with the advent of new shopping centers, so Pasaraya Sri Ratu is not being placed as primary option by the customers. The purpose of this research is to find out the influence of perceived quality and store environment against curtomer repurchase decisions through experiential marketing. Sampling techniques using non probability sampling with the kind of purposive sampling. The respondents in this study amounts to 100 respondents. Used analysis in this study is the Path Analysis using SPSS software 20.0 for Windows, where the validity test, reliability, coefficient of correlation, simple and multiple regression analysis, the determination coefficient, test of significance (t-test and F-test) in advance have been done previously. The results of this study indicate that the perceived quality (X1) and store environment (X2) partially or simultaneous affect experiential marketing (Z) and customer repurchase decisions (Y). In this research, Path analysis results represent that experiential marketing variable is an intervening variable against repeated purchasing decisions variable.